Fungi Associated With Different Parts of Cotton Seed (Dhaka University Journal of Biological Sciences, 2020)
Seed samples with highest (CB10), lowest (CB8), moderate fungal frequency (CB3) and randomly selected seeds from all varieties (CB1-14) were used. A total of 14 species of fungi, namely Aspergillus flavus Link, A. fumigatus Fresenius, A. niger Van Tiegh, Curvularia lunata (Wakker) Boedijn, Colletotrichum gloeosporioides Penz & Sacc, Fusarium nivale (Fr.) Sorauer, F. oxysporum Schlechtendal, F. fujikuroi Nirenberg, Penicillium aculeatum Raper & Fennell, Penicillium citrinum Thom, Rhizoctonia solani Khun., Rhizopus stolonifer (Ehrenb.) Vuill., Syncephalastrum racemosum Cohn and Trichoderma viride Pers. were found to be associated with seed parts of different varieties of cotton. The maximum ten species of fungi were isolated from seed coat. The most prevalent fungus was Rhizopus stolonifer which was found in all the parts of all the varieties of cotton seeds examined. Out of the 14 isolated fungi, Aspergillus flavus, A. fumigatus, A. niger, C. lunata, C. gloeosporioides, F. nivale, F. oxysporum, F. fujikuroi, Penicillium aculeatum, R. solani, R. stolonifer, S. racemosum and T. viride were found to be external and Aspergillus flavus, A. fumigatus, A. niger, C. lunata, F. nivale, Penicillium citrinum and R. stolonifer were internal seed borne fungi. Aspergillus flavus, A. fumigatus, A. niger, C. lunata, F. nivale and R. stolonifer were isolated as both external and internal seed borne fungi.Dhaka Univ. J. Biol. Sci. 29(2): 237-244, 2020 (July)